Protective enzyme activity regulation in cotton (Gossypium hirsutum L.) in response to Scirpus planiculmis stress - Zhang, Quancheng; Peng, Jun; Wang, Jungang (Frontiers in Plant Science, 2022)
Scirpus planiculmis, an important weed in rice and cotton fields, stresses crop growth and development, leading to yield loss. However, it is unclear how stressed plants respond to this weed. In this study, we analysed the stress effect of S. planiculmis on cotton under different weed densities, competition periods, and distribution conditions from the perspective of morphogenesis, physiological metabolism and crop yield. The effect of a low dose of herbicide on the relationship between cotton and S. planiculmis was also explored. The results showed that plant height, stem diameter, fresh weight, root length, boll number, single boll weight and yield of cotton all decreased with increasing S. planiculmis density and damage. The spatial distribution of S. planiculmis had no significant effect on plant height, stem diameter, fresh weight or root length of cotton, but crop yield loss decreased with increasing distance. S. planiculmis stress altered cotton chlorophyll, soluble protein and malondialdehyde (MDA) content, and protective enzyme activities. Compared with superoxide dismutase (SOD) and peroxidase (POD) activities, catalase (CAT) activity was increased under different S. planiculmis stress conditions. Therefore, we concluded that CAT plays a key role in protecting enzymes involved in defence responses. Under low-dose herbicide action, the activities of protective enzymes were increased, which helped cotton plants to resist S. planiculmis stress. The results revealed that regulating protective enzyme activities is important in cotton responses to S. planiculmis stress.